Not the opium of the people: Income and secularization in a panel of Prussian counties - Sascha O. Becker; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2013)
The interplay between religion and the economy has occupied social scientists for long. We construct a unique panel of income and Protestant church attendance for six waves of up to 175 Prussian counties spanning 1886-1911. The data reveal a marked decline in church attendance coinciding with increasing income. The cross-section also shows a negative association between income and church attendance. But the association disappears in panel analyses, including first-differenced models of the 1886-1911 change, panel models with county and time fixed effects, and panel Granger-causality tests. The results cast doubt on causal interpretations of the religion-economy nexus in Prussian secularization.
Keywords: Z12; N33; 330; religion; secularization; Prussian economic history